Antibacterial Activity Test of Extract Nyamplung (Calophyllum inophyllum Linn.) Leaves - Mutiara Novianti; Qurrotul Aini; Irma Fadhila Putri (ALCHEMY Jurnal Penelitian Kimia, 2015)
Phytochemical screening and antibacterial activity from ethanol extract of nyamplung (Callophylum inophyllum Linn.) leaves from Indonesia against Escherichia coli has been done. The extraction was done by soklet extraction using ethanol. Antibacterial activity test using the Optical Density method at λmax 600 nm. The result of phytochemical screening from ethanol extract showed that there were flavonoid compounds, saponins, tannins, phenols and triterpenoids. The result of antibacterial activity test showed that the optimum activity occurs at incubation time of 3 hours with percentase inhibition persentase i.e. 59.03 %.